Acolhimento institucional e desenvolvimento moral: a generosidade em crianças de quatro a seis anos de idade em situação de abrigo - Cabral, Clariana Morais Tinôco (2010)
This research has as main proposal to verify how the virtue of generosity, considered as one of the important aspects of moral development on children, shows itself in children between four and six years old in institutional welcome condition. Toward this aim, knowledge in Human Development Psychology, specifically Jean Piaget and his contemporary collaborators, were associated to philosophic knowledge, with emphasis in Kant and Aristotle. The research took place in an institutional welcome service in the town of Natal-RN, between February and May of 2009, witch is responsible to offer care to children from zero till six years old. As procedure were used: the rulebased game Memory Game ; the childhood story One note fight ; and observations of the institution s everyday. The corpus analysis was done by the Thematic Content Analysis method. In general, in the daily observations, children showed themselves more co-operative and generous than in the executed procedures, mainly when the matter subject was other´s well-being. The duty, Kantian perspective, was overcome by the Aristotelian sumo bem, classified as generous act of afford to other what is not posted as right, however guaranteed by solidarity